IMPROVING LEARNING OUTCOMES LEARNERS ON CHRISTIAN RELIGIOUS LESSON AND CHARACTERISTICS I CLASS IX THROUGH STRATEGY BUYER A JARAN COOPERATIVE TYPE OF JIG-SAW IN SMP STATE 45 MEDAN TP 2019/2020 - Rosdiana Sihombing (Sean Institute, 2022)
Improving the learning outcomes of students in Christian Religion and Morals in Class IX through the Jigsaw Type Cooperative Learning Strategy at SMP Negeri 45 Medan. The purpose of this research was to improve student learning outcomes in Class IX SMP Negeri 45 Medan in the 2019/2020 academic year. The method used in this study is the Classroom Action Research Method using 2 cycles, the subjects of this study were 22 students of class IX SMP Negeri 45 Medan, the instrument used was to obtain data is to use a test, observing the range of values ​​for the test is 1 - 100. The instrument used for data processing is to use the calculation of the number of student scores that have not been completed and the results of scores that have been completed. The results of this study indicate that there is an increase in learning outcomes with using a Jig-Saw cooperative learning strategy with the following results: (1) 80 % of students get a score of 60 Then (2) in the second cycle it increases to a value of 71.2 or reaches 84%.